INTELLIGENCE SYSTEM OF COTTAGE CHEESE QUALITY CONTROL - A. V. Ganicheva; A. V. Ganichev (Современная наука и инновации)
The need of creation of the automated system for diagnostics of cottage cheese quality is proved in the article. The inverse fuzzy inference method of dependence of the final product quality on the quality of the raw materials and the correctness of the technological process organization has been developed for the knowledge base.